2010
DOI: 10.1515/bmc.2010.026
|View full text |Cite
|
Sign up to set email alerts
|

Secreted bone morphogenetic protein antagonists of the Chordin family

Abstract: Chordin, Chordin-like 1, and Chordin-like 2 are secreted bone morphogenetic protein (BMP) antagonists with highly conserved Chordin-like cysteine-rich domains. Recently, Brorin and Brorin-like have been identified as new Chordinlike BMP antagonists. A Chordin ortholog, Short gastrulation, has been identified in Drosophila, a protostome, but not other orthologs. By contrast, Chordin, Chordin-like 1, and Chordin-like 2 have been identified in Ciona intestinalis, the closest living relatives of the vertebrates, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Although this notion has not been fulfilled and the entire concept of stable differentiation has been challenged, particularly due to the presence of different, highly plastic cell states that might be driven by different molecular alterations [8][9][10], the question remains as to how tumor cells evade these stemness-blocking cues. One factor that has been shown recently to be overexpressed in cancers, including GBM is the secreted BMP4 antagonist CHRDL1 [24,25]. Accordingly, our working hypothesis was that CHRDL1 acts as an enforcer of stemness in GSCs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although this notion has not been fulfilled and the entire concept of stable differentiation has been challenged, particularly due to the presence of different, highly plastic cell states that might be driven by different molecular alterations [8][9][10], the question remains as to how tumor cells evade these stemness-blocking cues. One factor that has been shown recently to be overexpressed in cancers, including GBM is the secreted BMP4 antagonist CHRDL1 [24,25]. Accordingly, our working hypothesis was that CHRDL1 acts as an enforcer of stemness in GSCs.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, it has been proposed that BMP4-treatment of GSCs induces asymmetric divisions favoring stem-like daughter cells [22], while Sachdeva et al propose that BMP signaling mediated by BMP4-treatment induces quiescence [23]. Notably, BMP proteins are antagonized by secreted proteins of the Chordin family [24] including CHRDL1 [25]. In particular, Cyr-Depauw et al showed that CHRDL1 inhibits migration and invasion of breast cancer cells via CHRDL1-mediated BMP4 inhibition [25].…”
Section: Introductionmentioning
confidence: 99%
“…siRNA GREM2 robustly promoted new bone formation compared to control groups [353]. Chordin (CHD) belongs to a family of proteins that share a cysteine-rich pro-collagen repeat (or chordin-like cysteine-rich repeat (CR)), which is also found in various extracellular matrix proteins [356,357]. Without exception, the homology between CHD family members, including chordin-like 1 (CHDL1) and chordin-like 2 (CHL2), lies within their CRs.…”
Section: Negative Regulation Of Bmp Signaling In Odontoblast Differen...mentioning
confidence: 99%
“…Without exception, the homology between CHD family members, including chordin-like 1 (CHDL1) and chordin-like 2 (CHL2), lies within their CRs. The CRs within CHD and CHDLs are responsible for BMP binding, specifically and Chordin (CHD) belongs to a family of proteins that share a cysteine-rich pro-collagen repeat (or chordin-like cysteine-rich repeat (CR)), which is also found in various extracellular matrix proteins [356,357]. Without exception, the homology between CHD family members, including chordin-like 1 (CHDL1) and chordin-like 2 (CHL2), lies within their CRs.…”
Section: Negative Regulation Of Bmp Signaling In Odontoblast Differen...mentioning
confidence: 99%
“…Additionally, it has been proposed that BMP4 treatment of GSCs induces asymmetric divisions favoring stem-like daughter cells [ 22 ], while Sachdeva et al proposed that BMP signaling mediated by BMP4-treatment induces quiescence [ 23 ]. Notably, BMP proteins are antagonised by secreted proteins of the Chordin family [ 24 ], including CHRDL1 [ 25 ]. In particular, Cyr-Depauw et al showed that CHRDL1 inhibits the migration and invasion of breast cancer cells via CHRDL1-mediated BMP4 inhibition [ 25 ].…”
Section: Introductionmentioning
confidence: 99%